The Implementation of the ARCS Model in Indonesian Language Learning to Enhance Literacy Skills of Fifth-Grade Students at Elementary School - Muhammad Romli; I Nyoman Sudiana; Ida Bagus Putrayasa (Universitas Cokroaminoto Palopo, 2024)
This study aims to analyze the impact of the ARCS (Attention, Relevance, Confidence, Satisfaction) learning model on the literacy skills of fifth-grade students in Indonesian language learning, with learning motivation as a control variable. Employing a quasi-experimental approach with a pretest-posttest control group design, this research involved two groups: the experimental group taught using the ARCS model and the control group taught using conventional methods. A total of 56 students from SDN Parsanga II participated, equally divided between the two groups. Data collection instruments included literacy tests and learning motivation questionnaires. The findings reveal a significant difference in literacy skills between students taught using the ARCS model and those taught using conventional methods. Statistical analysis, including ANCOVA, showed that the ARCS model significantly improved literacy skills, with an F-value of 29.102 and p < 0.05. Furthermore, the R Squared value of 0.355 indicates that the ARCS model and learning motivation together accounted for 35.5% of the variability in literacy skills. The four stages of the ARCS model—Attention, Relevance, Confidence, and Satisfaction—were instrumental in enhancing students’ literacy. These stages effectively captured students' attention, linked learning materials to their lives, built confidence in tackling texts, and provided a satisfying learning experience. The study highlights the effectiveness and flexibility of the ARCS model in improving literacy skills in elementary education. By fostering motivation and creating meaningful learning experiences, the ARCS model serves as a promising solution to address literacy challenges in elementary schools, contributing to better academic outcomes.